A standardised flexibility assessment methodology for demand response. Issue 1 (30th May 2019) - O'Connell, Sarah; Reynders, Glenn; Seri, Federico; Sterling, Raymond; Keane, Marcus M.
Abstract : Purpose: The purpose of this paper is to standardised four-step flexibility assessment methodology for evaluating the available electrical load reduction or increase a building can provide in response to a signal from an aggregator or grid operator. Design/methodology/approach: The four steps in the methodology consist of Step 1: systems, loads, storage and generation identification; Step 2: flexibility characterisation; Step 3: scenario modelling; and Step 4: key performance indicator (KPI) label. Findings: A detailed case study for one building, validated through on-site experiments, verified the feasibility and accuracy of the approach. Research limitations/implications: The results were benchmarked against available demonstration studies but could benefit from the future development of standardised benchmarks. Practical implications: The ease of implementation enables building operators to quickly and cost effectively evaluate the flexibility of their building. By clearly defining the flexibility range, the KPI label enables contract negotiation between stakeholders for demand side services. It may also be applicable as a smart readiness indicator. Social implications: The novel KPI label has the capability to operationalise the concept of building flexibility to a wider spectrum of society, enabling smart grid demand response roll-out to residential and small commercial customers. Originality/value: This paper fulfils an identified need for an early stage flexibility assessment which explicitly includes source selection that can be implemented in an offline manner without the need for extensive real-time data acquisition, ICT platforms or additional metre and sensor installations.